Identifikasi Kandungan Merkuri Pada Krim Pemutih Tanpa BPOM Yang Beredar Di Kota Bengkulu - Nita Anggreani; Ririn Okta Vira (CV. Multi Kreasi Media, 2026)
The use of skin-lightening creams, particularly among women, is on the rise. Some manufacturers incorporate hazardous substances, such as mercury (Hg), into these products because they can achieve a whitening effect at a low cost. This study was conducted to identify the mercury content in skin-lightening creams circulating in Bengkulu City. Samples were collected using purposive sampling—specifically, skin-lightening creams without BPOM registration numbers that are most frequently purchased in Bengkulu City. A total of four skin-lightening cream samples were analyzed. Qualitative analysis using a color test with a KI solution on all samples produced a reddish-orange precipitate, indicating a positive result for mercury. Mercury levels in the samples were measured using UV-Vis spectrophotometry, with the highest result found in Sample C at 39,130.4 mg/kg and the lowest in Sample A at 3,967.39 mg/kg. These results indicate that all samples contained mercury levels far exceeding the threshold limit (1 mg/L or 1 mg/kg) as stipulated in Law No. 12 of 2019.